1993
DOI: 10.1002/jccs.199300050
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Porphyrin Discotic Liquid Crystals: Photoinduced Charge Separation and Trapping

Abstract: Individual members of a family of highly absorptive porphyrins bearing symmetrically positioned flexible side chains form discotic liquid crystalline mesophases at modest temperature ranges. The order of this phase is preserved when a thin layer of this self‐assembled material is cooled to room temperature. Exposure of such films to visible excitation, with or without an externally applied electrical field, produces photovoltaic effects and/or charge trapping. The latter effect constitutes the basis for optoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It then took until 1987, when Gregg et al reported porphyrin octaesters as new discotic liquid crystals . Since then a huge variety of porphyrin derivatives have been explored and progress has been summarized previously. , In 2009 Shearman et al reported the phase transition behavior of β-octaalkyl porphyrins 206 and 207 (Scheme ). Whereas the free macrocycles 206 were nonmesomorphic, the corresponding Zn complexes 207 displayed Col r phases.…”
Section: Classes Of Compoundsmentioning
confidence: 99%
“…It then took until 1987, when Gregg et al reported porphyrin octaesters as new discotic liquid crystals . Since then a huge variety of porphyrin derivatives have been explored and progress has been summarized previously. , In 2009 Shearman et al reported the phase transition behavior of β-octaalkyl porphyrins 206 and 207 (Scheme ). Whereas the free macrocycles 206 were nonmesomorphic, the corresponding Zn complexes 207 displayed Col r phases.…”
Section: Classes Of Compoundsmentioning
confidence: 99%
“…From a molecular perspective, several scaffolds have turned out to be successful candidates for the nanosegregation, which ultimately led into the formation of columnar mesophases. Besides tri- and hexasubstituted benzenes, in particular triphenylenes [ 10 ], perylenes [ 11 ], hexa- peri -hexabenzocoronenes [ 12 , 13 ], porphyrins [ 14 , 15 ], phthalocyanines [ 15 ], quinoxalines and other aza analogues of polycyclic aromatic hydrocarbons were used as mesogenic subunits. However, not only disk-shaped mesogens, but also non-conventional [ 16 ] and supramolecular and hydrogen bonded liquid crystals [ 17 ] can self-assemble into columnar aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Organic compounds have been discussed as potential candidates for application as components of electronic devices for over a decade . The high degree of organization of the investigated systems, such as Langmuir−Blodgett (LB) films or liquid crystals, is a prerequisite for a good performance of the material. Recently, discotic liquid crystals have been discussed as new materials in photoconducting systems and photovoltaic instruments .…”
Section: Introductionmentioning
confidence: 99%